A Prospective Randomized Trial of Imipenem-Cilastatin Versus Clindamycin/Tobramycin in the Treatmentof Intra-Abdominal and Pelvic Infections - Lionel A Mandell; Pierre L Turgeon; Allan R Ronalds; The Canadian Clinical Trials Group (Canadian Journal of Infectious Diseases)
Objective: A Canadian multicentre clinical trial in the treatment of intra-abdominal and pelvic infections to compare the efficacy and safety of monotherapy using imipenem-cilastatin (imipenem) (500 mg intravenously every 6 h) versus combination therapy with clindamycin/tobramycin (clindamycin 600 mg intravenously every 6 h and tobramycin 1.7 mg/kg intravenously every 8 h).